Researchers and their data: A study based on the use of the word data in scholarly articles - Bordignon, Frédérique; Maisonobe, Marion (Quantitative Science Studies, 2022)
Abstract Data is one of the most used terms in scientific vocabulary. This article focuses on the relationship between data and research by analyzing the contexts of occurrence of the word data in a corpus of 72,471 research articles (1980–2012) from two distinct fields (Social sciences, Physical sciences). The aim is to shed light on the issues raised by research on data, namely the difficulty of defining what is considered as data, the transformations that data undergo during the research process, and how they gain value for researchers who hold them. Relying on the distribution of occurrences throughout the texts and over time, it demonstrates that the word data mostly occurs at the beginning and end of research articles. Adjectives and verbs accompanying the noun data turn out to be even more important than data itself in specifying data. The increase in the use of possessive pronouns at the end of the articles reveals that authors tend to claim ownership of their data at the very end of the research process. Our research demonstrates that even if data-handling operations are increasingly frequent, they are still described with imprecise verbs that do not reflect the complexity of these transformations.